Analisis Penerapan Akuntansi Pajak Tangguhan Pada Laporan Keuangan PT. Maju Mobilindo - Deaz Fetrin Hertiningrum; Maulan Irwadi; Muhammad Hamdan Sayadi (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to investigate the application of deferred tax accounting in the financial statements of PT. Maju Mobilindo in 2017-2018. The data used comes from the financial statements of PT. Maju Mobilindo in 2017 and 2018. This research method is descriptive qualitative. The results showed that the company did not recognize the previous year's tax and current tax, so the company did not apply PSAK No.46 but instead applied SAK ETAP. Based on the calculation in the income statement, the company experienced a fiscal loss in 2017 of Rp. 7,101,511,733, -and 2018 amounting to Rp. 12,021,312,865, - which is based on Article 6 paragraph (2) of Law Number 36 the Year 2008 concerning Income Tax, so that companies are not subject to income tax, and this has resulted in the company not applying deferred tax. Therefore, it is better if the company makes an increase in sales so that the company gets a profit and can contribute to increasing state revenue by payingtaxes.